Limites au ciblage - Roch, Alain (Assurances, 1993)
This paper deals with targeting Iimits as regards the disclosure of personal information. It describes legal measures European countries have adopted to protect the public and private sectors. The author also comments on the situation in Canada and focuses on Quebec where a Law was adopted for the public sector only. He exposes the lack of legislation in the private sector in this area and the forthcoming provisions in the Quebec Civil Code, expected in early 1994.